Euclides Roxo: engineer, teacher, intellectual, and mathematics educator Euclides Roxo: engenheiro, professor, intelectual e educador matemático - Bruno Alves Dassie; João Bosco Pitombeira Fernandes de Carvalho (Universidade Estadual Paulista, 2010)
This paper presents Euclides Roxo's professional life, taking into account his past experiences before he became an educational reformer. We describe the work possibilities for engineers in Brazil at the beginning of the 20th Century to show that Roxo's option for a teaching career was influenced by the society in which he lived. On the other hand, his years as a teacher at the Instituto de Educação in Rio de Janeiro are essential to study the evolution of Roxo's educational ideas, since this institution provided him with the necessary stimulus for the development of his ideas. We also briefly present some of his other educational activities. We think we can justly claim that Euclides Roxo was an intellectual working as a mathematics teacher, indeed a mathematics educator. Keywords: Euclides Roxo. History of mathematics education. mathematics educator. Institutionalization of mathematics teachers. Este artigo apresenta a trajetória profissional de Euclides Roxo considerando fatos que precederam sua atuação como reformador educacional. São apresentadas considerações sobre o mercado de trabalho do engenheiro no início do século XX, para mostrar que a opção de Euclides Roxo pelo magistério não foi autônoma em relação ao quadro da sociedade da época. Por outro lado, sua atuação no Instituto de Educação do Rio de Janeiro, antiga Escola Normal, é essencial para analisar a gênese de suas idéias, pois esta instituição apresentou um ambiente educacional propício. Por fim, apresentamos de forma breve outras instâncias de atuação de Euclides Roxo. Dessa forma, podemos considerar Euclides Roxo como um intelectual atuante no ensino da matemática, ou seja, um educador matemático. Palavras-chave: Euclides Roxo. História da Educação Matemática. Institucionalização do professor de matemática. Educador Matemático.